Reconstruction of the Adult Hemifacial Microsomia Patient with Temporomandibular Joint Total Joint Prosthesis and Orthognathic Surgery. (15th March 2018) - Cascone, Piero; Vellone, Valentino; Ramieri, Valerio; Basile, Emanuela; Tarsitano, Achille; Marchetti, Claudio
Abstract : Background . HFM patients' reconstruction has always been a challenge for maxillofacial surgeons, and numerous reconstructive techniques have been described. Surgical treatment depends on the patient's age and contemplates Temporomandibular Joint (TMJ) reconstruction in conjunction with orthognathic surgery, usually necessary following completion of growth to maximize the functional and esthetic results. Distraction osteogenesis had gained popularity as valid alternative in growing patients, but the two primary methods to reconstruct the TMJs involve the use of autogenous, using free or microvascular bone grafts, or alloplastic graft, but there is no widely accepted method. Methods . The increasing use of temporomandibular prosthesis for temporomandibular problems has led us to use them even in HFM. A case of female nongrowing patients with HFM type IIb treated with temporomandibular prosthesis in an all-in-one protocol is presented. Results . Incisal opening, measured with BioPAK system (Bioresearch Inc., Milwaukee, USA), was 21.4 mm in the presurgical period and 32.2 mm after all-in-one procedure, for an increase of 50.5%. Excursive movement to the right side was 2.2 mm in the presurgical period and was 1.5 mm after surgery, for a decrease of 31.8%. Left excursion movement changed from 5 mm to 6.1 mm, for an increase of 22.0%. Conclusions . The TMJ Concepts patient-fitted TJP in conjunction with orthognathic surgery for TMJ and jaw reconstruction is a valid option for patients with HFM.